THE CORRELATION OF THE LECTURERS’ TEACHING METHODS AND COMPETENCIES TO THE STUDENTS’ LEARNING ACHIEVEMENT - Mindani, Mindani; Trinova, Zulvia; Lindra, Afni; Alimir, Alimir (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract: The lecturers’ teaching methods and competencies vary at IAIN Bukittinggi so that it is important to know the correlation of the lecturers’ teaching methods and competencies to the students’ learning achievement at IAIN Bukittinggi. The method used of this research was quantitative method with ex post facto design. This research involved all lecturers and students of IAIN Bukittinggi as population and the sample was consisted of 40 people. The instrument used to collect the data was closed-questionnaire. The data were processed by scoring and inferential analyzing. The finding indicated that most of the lecturers at IAIN Bukittinggi applied lecture, question-answer, discussion, assignment, and problem solving methods. It was also found that the correlation of the lecturers’ teaching methods and competencies to the students’ achievement was only 2.8%. Therefore, there was low correlation of the lecturers’ teaching methods and competencies to the students’ achievement in IAIN Bukittinggi. Abstrak: Metode dan kompetensi mengajar dosen bervariasi di IAIN Bukittinggi sehingga penting untuk mengetahui hubungan antara metode pengajaran dan kompetensi dosen dengan prestasi belajar mahasiswa di IAIN Bukittinggi. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan desain ex post facto. Penelitian ini melibatkan semua dosen dan mahasiswa IAIN Bukittinggi sebagai populasi dan sampel terdiri dari 40 orang. Instrumen yang digunakan untuk mengumpulkan data adalah kuesioner tertutup. Data diproses dengan penilaian dan analisis inferensial. Temuan menunjukkan bahwa sebagian besar dosen di IAIN Bukittinggi menerapkan metode ceramah, tanya jawab, diskusi, penugasan, dan pemecahan masalah. Ditemukan juga bahwa korelasi antara metode pengajaran dan kompetensi dosen dengan prestasi belajar siswa hanya 2,8%. Oleh karena itu, ada korelasi yang rendah antara metode pengajaran dan kompetensi dosen dengan prestasi siswa di IAIN Bukittinggi.